2005
DOI: 10.1044/1092-4388(2005/033)
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age and Hearing Loss on Gap Detection and the Precedence Effect

Abstract: Deficits in temporal resolution and/or the precedence effect may underlie part of the speech understanding difficulties experienced by older listeners in degraded acoustic environments. In a previous investigation, R. Roberts and J. Lister (2004) identified a positive correlation between measures of temporal resolution and the precedence effect, specifically across-channel gap detection (as measured dichotically) and fusion. Across-channel gap detection may also be measured using frequency-disparate markers. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
60
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 43 publications
6
60
1
1
Order By: Relevance
“…Most interesting in light of the present results are the behavioral findings for older adults. This group often has poorer within-and across-channel gap detections than young adults; yet, age-group differences are much larger for acrosschannel than within-channel conditions (e.g., Lister & Roberts, 2005;Lister, et al, 2002).As within-and across-channel performance was not correlated in the present study (r = 0.22, p = 0.50) or others (Phillips & Smith, 2004), it is likely that different mechanisms are involved in the two tasks. The present study represents a first step in the investigation of the physiological underpinnings of across-channel gap detection.…”
contrasting
confidence: 43%
See 2 more Smart Citations
“…Most interesting in light of the present results are the behavioral findings for older adults. This group often has poorer within-and across-channel gap detections than young adults; yet, age-group differences are much larger for acrosschannel than within-channel conditions (e.g., Lister & Roberts, 2005;Lister, et al, 2002).As within-and across-channel performance was not correlated in the present study (r = 0.22, p = 0.50) or others (Phillips & Smith, 2004), it is likely that different mechanisms are involved in the two tasks. The present study represents a first step in the investigation of the physiological underpinnings of across-channel gap detection.…”
contrasting
confidence: 43%
“…The shortest gap that a listener can detect (relative to the standard) is called a gap detection threshold (GDT). Psychophysical GDTs are influenced by a number of stimulus factors, including marker bandwidth (Eddins, Hall, & Grose, 1992;Snell, Ison, & Frisina, 1994), marker duration (He, Horwitz, Dubno, & Mills, 1999), monotic, diotic, or dichotic presentation modes (Gordon-Salant & Fitzgibbons, 1999;He, et al, 1999;Lister & Roberts, 2005), and the spectral similarity of the markers before and after the gap (Lister, Besing & Koehnke, 2002;Oxenham, 2000).…”
Section: Author Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the HI listeners in this study were on average older than the NH listeners in the study by Wojtczak et al (2012) used as a control group. A large number of studies have reported clear effects of age on gap detection and gap-duration discrimination for both within-channel and across-channel markers (Fitzgibbons and Gordon-Salant 1994;Schneider et al 1994;He et al 1999;Lister et al 2000Lister et al , 2002Lister and Roberts 2005). Since the NH and HI listeners compared in this study were not age-matched, some of the observed differences between their data may reflect poorer coding of temporal information or a reduced ability to integrate temporal information across frequency due to the age of the HI listeners.…”
Section: Age Versus Hearing Lossmentioning
confidence: 73%
“…However, deficits due to cochlear hearing loss have been shown in tasks involving comparisons of temporal information across frequency, although not consistently. Across-channel gap detection and gap-duration discrimination measured with frequency-disparate markers preceding and following silent gaps have been shown to be unaffected by hearing loss (Lister et al 2002;Lister and Roberts 2005). Similarly, the ability to detect a difference in temporal envelope patterns in the presence of an interfering modulation in the remote frequency region is comparable for the NH and HI listeners (Grose and Hall, 1996).…”
Section: Cochlear Hearing Loss and Processing Of Temporal Informationmentioning
confidence: 99%